1993
DOI: 10.1155/tsm.22.113
|View full text |Cite
|
Sign up to set email alerts
|

Development of a {111} Recrystallization Texture Associated WithDynamic Strain Aging During Hot Rolling in the Ferrite Region

Abstract: Hot rolling in the ferrite region is applied in an extra-low C sheet steel without cold rolling by employing dynamic strain aging. When the amount of solute C is about 10 ppm before rolling, the r-value and 222 intensity ratio of sheet steel annealed after rolling are maxima at the rolling temperature of 773K, during which dynamic strain aging occurs. The {222} residual strain in the specimen rolled at 773K is higher than that in specimens rolled at other temperatures. It is proposed that dynamic strain aging … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…[1][2][3][4][5][6][7][8][9][10][11][12] It has been found that cold-rolled sheet steels with extra-high r-values can be manufactured by hot rolling in the ferrite region with lubrication. [4][5][6][7] It is known that dynamic recovery easily occurs at higher temperatures during ferritic hot rolling, in which the steel has a bcc crystal structure. If the amount of dynamic recovery increases, the rolling texture can be expected to differ from that of cold-rolled sheets.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12] It has been found that cold-rolled sheet steels with extra-high r-values can be manufactured by hot rolling in the ferrite region with lubrication. [4][5][6][7] It is known that dynamic recovery easily occurs at higher temperatures during ferritic hot rolling, in which the steel has a bcc crystal structure. If the amount of dynamic recovery increases, the rolling texture can be expected to differ from that of cold-rolled sheets.…”
Section: Introductionmentioning
confidence: 99%